KITOB DISTRICT TOURISM CAPACITY: VISITORSHIP, AGROTURISM AND SUSTAINABLE DEVELOPMENT STRATEGY (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article analyzes the tourism potential of Kitab district based on pilgrimage and agrotourism. The natural, geographical, historical and cultural resources of the region are assessed, and strategies for their effective use and sustainable development are proposed. The issues of developing tourism infrastructure and increasing the participation of the local population are also covered.